Síntese, caracterização e testes eletroquímicos de dióxido de manganês nanométrico como material de eletrodo de supercapacitores - Zutim, Paulo (2018)
Manganese dioxide was synthesized by a microwave-hydrothermal method using alternative, unprecedented and completely soluble reagents. For such, potassium permanganate and acetone were dissolved in different proportions (4:1,5; 4:3; 4:4 and 4:7,) and treated in a microwave reactor, under magnetic stirring, at different temperatures (100, 140 and 160 °C), synthesis times (1, 3, 5 and 10 min) and porcentage of the vessel volume occupied by the reactional mixture (60 and 80%). The obtained materials have been characterized by X-ray diffraction, scanning and transmission electron microscopies, electron diffraction, thermogravimetry, determination of specific area, cyclic voltammetry, and charge and discharge at constant current. The X-ray diffractogramms of the evaluated materials were associated with the JCPDS card number 421317 for MnO2 phase potassium birnessita. The synthesized materials also presented, according to others characterization analyses, nanosized particles (with hierarchical structure), presence of adsorbed and crystalline water and a specific area of 108 m2 g–1, being desirable features for electrode materials of supercapacitors. In order to improve the reproducibility of specific capacitance (c) values the electrodes preparation methodology was also studied. The best results were obtained for electrodes containing 75% MnO2, 20% acetylene black and 5% PVDF confectioned by the methodology of dropping followed by spinning and using a acetylene black of lower average particle size. The product of the synthesis performed at 100 °C over 10 min with the reactional vessel filled with 60% of its total capacity presented the best results as active material for supercapacitor electrode, with a c value of (17 ± 1) x 101 F g–1 (0,2 g–1 ) and a charge retention of 81 % after 5000 charge and discharge cycles at 1 A g–1.